Analysis of Marketing Mix and Creativity towards MSME Business Development in Medan City - Dian Sari; Irawan (Penerbit Jurnal Indonesia, 2024)
The study aims to explore the influence of Marketing Mix and Creativity on MSME Business Development in Medan Perjuangan